Relationship Between Teacher Professionalism and Performance in Elementary Schools - Dara Sartika; Muhammad Ihsan Dacholfany; Sujino Sujino (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study investigates the relationship between certified teacher professionalism and teacher performance in elementary schools. A quantitative approach with a correlational design was employed. The sample consisted of 52 certified teachers selected through total sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Pearson Product Moment correlation analysis was conducted with the aid of Microsoft Excel. The findings reveal a positive and significant relationship between certified teacher professionalism and teacher performance (r = 0.755 > r table = 0.273; p < 0.05), categorized as a strong correlation. Teacher professionalism contributed 57% to teacher performance. These results highlight the crucial role of enhancing teacher professionalism in improving performance within elementary education.